PENGGUNAAN METODE QUEEN REARING TERHADAP PEMBENTUKAN SEL RATU APIS MELLIFERA UNTUK PENGEMBANGAN PERLEBAHAN - Rompas, Joice J.I.; Maramis, R. T.D. (ZOOTEC, 2015)
UTILIZING METODE QUEEN REARING APIS MELLIFERA FOR BEES DEVELOPMENT. This research was conducted in Kumelembuai Village KumelembuaiSubdistrictof  SouthMinahasa Regency that took place from Desember 2012 to January 2014. Completely Randomized Design was used with F test or Kruskal Wallis test. Significant differences were tested using the DuncanTest. Queen Rearing method superior that is Emergency Cell method. Each method consisted of seven treatments with four replicates. The seven treatments were : (a). 200 grams of cane sugar + 200 gram of water, (b). 100 grams of cane sugar + 200 grams of water, (c). 66 grams of cane sugar + 200 grams of water, (d). 200 grams of arenga sugar + 200 grams of water, (e). 100 grams of arenga sugar + 200 grams of water,  (f). 66 grams of arenga sugar + 200 grams of water,  (g). Control. Key  Word :  Apismellifera F., Queen Rearing Method